ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY ON THE FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES WITH RATIONAL FINANCING MEDIATION DECISIONS AND FINANCIAL CAPITAL IN DELI SERDANG DISTRICT, NORTH SUMATRA PROVINCE - Novian Paisal Sitompul; Khaira Amalia Fachrudin; Nisrul Irawati (CV. Radja Publika, 2024)
This research aims to analyze the influence of financial literacy on the financial performance of small and medium enterprises with the mediation of rational financing decisions and financial capital in Deli Serdang Regency, North Sumatra Province. The type of research used is quantitative associative research. The data analysis techniques used are descriptive statistical methods and structural equation modeling (SEM) analysis. The sample in this research was 100 Small and Medium Enterprises (UKM) with a sampling technique using purposive sampling. The research results show that financial literacy has a positive and significant effect on rational financing decisions. Financial literacy has a positive and significant effect on financial capital. Financial literacy has a positive and significant effect on financial performance. Rational financing decisions have a positive and significant effect on financial performance. Financial capital has a positive and significant effect on financial performance. Financial literacy influences financial performance mediated by rational financing decisions. Financial literacy influences financial performance mediated by financial capital.